PERSEPSI PETANI KENTANG DALAM PEMBERDAYAAN KELOMPOK TANI GEMAH RIPAH II DESA NGANTRU - A. Yusuf Kholil; Hendra Hendra (OPTIMA, 2020)
This research purposes to determine potato farmers' perceptions in empowering in the Gemah Ripah II Farmer Group in Ngantru Village, Ngantang District, Malang Regency. Perception is the process concerned about the entry of messages or information into the human brain, through human perceptions that are constantly in a relationship with their environment. This perception process occurs by looking at the analysis of the primary data obtained by taking data directly with potato farmers who are members of a group of 30 Gemah Ripah farmers. Each farmer respondent got 15 questions and was immediately answerable then the results of the answers were processed and analisys using the SPSS software, the data processing purposes to prove potato farmers' perceptions in empowering potato farmers in Gemah Ripah II Farmer Groups in Ngantru Village, Ngantang District, Malang Regency. Looking at the results of data processing, it can be concluded that the highest percentage of potato farmers' perceptions of the efforts of extension agents in empowering potato farmers is 48.67%. This shows that potato farmers' perceptions of the empowering farmers in the Gemah Ripah II Farmer Group are good.